TURMERIC AND ITS PHARMACOLOGICAL PROPERTIES - A REVIEW - Ram V, Vamshi; S, Preetha (International Journal of Psychosocial Rehabilitation, 2020)
Turmeric is a flowering plant, Curcuma longa of the ginger family, Zingiberaceae, the roots of which are used in cooking. The plant is a perennial, rhizomatous, herbaceous plant local to the Indian subcontinent and Southeast Asia that calls for temperatures between 20 and 30 °C (68 and 86 °F) and a large amount of annual rainfall to thrive. Plants are gathered each year for their rhizomes, a few for propagation in the following season and some for consumption. This is a review-based study on the topic of turmeric over viral diseases. Articles based on turmeric were referred to completely, which were taken from “PubMed,” “Google Scholar,” and PMC. Around 20-25 articles were referred. Other articles that have done a study on the medicinal and pharmacological properties of turmeric are also compared. Hence turmeric has a wide range of biological activities that can be used for the preparation of various formulations for the treatment of various conditions.